Mutual Scholastic Background Between Executives and Auditors in Audit Fees Settings - Hendi Hendi; Budi Harsono; Novi Novi (Value : Jurnal Manajemen dan Akuntansi, 2026)
This study investigates how social connections between senior executives particularly chief executive officers (CEOs) and chief financial officers (CFOs), audit committee (ACs) and external auditors, stemming from shared educational backgrounds, influence the determination of audit fee in Indonesian listed firms. Audit fees are used as a proxy for audit effort and risk assessment. By situating the analysis within Indonesia’s relationship-based institutional context, this study contributes to the literature on auditor and client relationships and audit pricing in emerging markets. Utilizing panel data from 110 firms over the 2019–2023 period, the analysis applies descriptive statistics, Pearson correlation, and multiple regression techniques. The findings indicate that educational ties between CFOs and auditors have a positive and significant effect on audit fees, while CEO, audit committee and auditor ties are insignificant. These effects are more pronounced in firms audited by Big Four networks and in larger, better-performing companies. The results underscore that educational based relational embeddedness influences audit pricing behavior in emerging market.